Investigation of STRAUS-2 pulsed electron accelerator characteristics - Gordeev, V.S.; Myskov, G.A.; Filippov, V.O.; Averchenkov, V.Ya. (Вопросы атомной науки и техники, 1999)
Last years a successful development of highvoltage pulse forming techniques based on stepped transmission lines led to creation of a set of powerful and compact electrophysics facilities including a highcurrent pulsed electron accelerator STRAUS-2 [1, 2]. The first sample of this accelerator was started up into exploitation in 1989. At present, three facilities of the same type exist in VNIIEF, one of them is used as an injector for a linear induction accelerator LIA-10M [2-5]. Two others are autonomous and applied for research in radiation physics.